Detection of Leishmania metacyclogenesis within the sand fly vector employing a real-time PCR for sherp gene expression: A tool for Leishmania surveillance and transmission potential. - Chukwunonso O Nzelu; Somayeh Bahrami; Phillip G Lawyer; Nathan C Peters (PLoS Neglected Tropical Diseases)
Surveillance of infected insect vectors of vector-transmitted diseases has been recognized for its ability to estimate pathogen prevalence and transmission potential. Classically restricted to microscopic dissection and examination of individual insects, the potential of entomological monitoring has grown due to the advent of rapid molecular DNA detection methods with high specificity and sensitivity. Despite such advancement, a recurring question concerning DNA detection of parasitic pathogens is related to the fact that DNA amplification, by itself, does not differentiate between insects carrying infectious versus dead, non- or poorly-infectious life-cycle stages, thereby limiting it's programmatic usefulness for accurately measuring the transmission potential of infected insects in endemic areas or within experimentally infected populations. Herein, we developed a quantitative real-time PCR with Reverse Transcription (RT-qPCR) based sherp (small hydrophilic endoplasmic reticulum-associated protein) detection assay employing a novel set of sherp-RT-qPCR primers to detect and quantify infectious Leishmania parasites in infected vector sand flies. The sherp RT-qPCR showed significantly increased expression of sherp transcripts in infectious Leishmania metacyclic versus non-metacyclic promastigotes or mammalian-derived amastigotes. The assay displayed detection performance ranging from 106 to 1 parasite and could reliably quantify parasites within infected sand flies without the need for dissection. Sherp transcripts were also successfully amplified from flies stored in ethanol at room temperature, a practical and economical method of sample preservation in resource-limited field settings. Lastly, in conjunction with an established RT-qPCR assay for Leishmania kinetoplast DNA minicircles, we were able to calculate a score for the degree of metacyclogenesis within infected sand flies, a known predictor of transmission potential. These results highlight the potential of the sherp-RT-qPCR assay to identify hotspots of potential transmission, areas of re-emergence, vector competence, and the transmission potential of infected sand fly populations.